Sensing in Sacral Neuromodulation: A Feasibility Study in Subjects With Urinary Incontinence and Retention - Goudelocke, Colin; Jungbauer Nikolas, Lisa M.; Bittner, Katie C.; Offutt, Sarah J.; Miller, Anne E.; Slopsema, Julia P. (Neuromodulation (Malden, Mass.), 2024)
Sacral neuromodulation (SNM) therapy standard of care relies on visual-motor responses and patient-reported sensory responses in deciding optimized lead placement and programming. Automatic detection of stimulation responses could offer a simple, consistent indicator for optimizing SNM. The purpose of this study was to measure and characterize sacral evoked responses (SERs) resulting from sacral nerve stimulation using a commercial, tined SNM lead. A custom external research system with stimulation and sensing hardware was connected to the percutaneous extension of an implanted lead during a staged (tined lead) evaluation for SNM. The system collected SER recordings across a range of prespecified stimulation settings (electrode configuration combinations for bipolar stimulation and bipolar sensing) during intraoperative and postoperative sessions in 21 subjects with overactive bladder (OAB) and nonobstructive urinary retention (NOUR). Motor and sensory thresholds were collected during the same sessions. SERs were detected in all 21 subjects. SER morphology (number of peaks, magnitude, and timing) varied across electrode configurations within and across subjects. Among subjects and electrode configurations tested, recordings contained SERs at motor threshold and/or sensory threshold in 75% to 80% of subjects. This study confirmed that implanted SNM leads can be used to directly record SERs elicited by stimulation in subjects with OAB and NOUR. SERs were readily detectable at typical SNM stimulation settings and procedural time points. Using these SERs as possible objective measures of SNM response has the capability to automate patient-specific SNM therapy, potentially providing consistent lead placement, programming, and/or closed-loop therapy.